2017
DOI: 10.1002/cncr.30843
|View full text |Cite
|
Sign up to set email alerts
|

Treatment at high‐volume facilities and academic centers is independently associated with improved survival in patients with locally advanced head and neck cancer

Abstract: Patients with locally advanced head and neck squamous cell carcinoma who are undergoing curative radiotherapy at HVFs and academic centers appear to have improved survival. Cancer 2017;123:3933-42. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
140
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(150 citation statements)
references
References 42 publications
9
140
0
1
Order By: Relevance
“…Whereas prior literature has forecasted an epidemic, this analysis highlights that non-oropharyngeal HNSCCs are becoming increasingly rare in the US and OPSCC remain rare. This in combination with the extensive data regarding survival benefits for high-volume centers 1719 support the need for centralized care of HNSCC patients.…”
Section: Discussionmentioning
confidence: 76%
“…Whereas prior literature has forecasted an epidemic, this analysis highlights that non-oropharyngeal HNSCCs are becoming increasingly rare in the US and OPSCC remain rare. This in combination with the extensive data regarding survival benefits for high-volume centers 1719 support the need for centralized care of HNSCC patients.…”
Section: Discussionmentioning
confidence: 76%
“…Some studies investigated the association between patient's outcomes and provider/physician volume, 2 institutional clinical trial volume, 3,17 or hospital volume. 7 These data confirm the importance of treatment expertise outside the context of a clinical trial. 21 Recently, an analysis conducted in the United States employing the National Cancer Database showed that patients undergoing curative radiotherapy at high-volume facilities and academic centers showed an increased survival.…”
Section: Discussionmentioning
confidence: 61%
“…[34][35][36][37] We have previously reported that speech-language pathology care was associated with high-volume care, a reduced odds of dysphagia, and improved survival in elderly patients with OPSCC. The majority of patients in this cohort were nonsmokers with little to no documented comorbidity, 10 which raises the possibility that the majority of these patients had human papillomavirus (HPV)-associated tumors with good performance status and were more resilient to the effects of treatment-related toxicity, and more responsive to process measures associated with higher quality care that address complications of care.…”
Section: Discussionmentioning
confidence: 99%